2021
DOI: 10.1155/2021/9473508
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Importance of MicroRNAs as Novel Indicators How to Manage Patients with Juvenile Idiopathic Arthritis More Effectively

Abstract: Small, noncoding sequences of ribonucleic acid called microRNAs (miRNAs, miR) are functioning as posttranscriptional regulators of gene expression. As they draw increasing attention of rheumatologists, there is a growing body of evidence concerning specific molecules that may affect the long-term care of patients with inflammatory arthritides. Findings involving children with juvenile idiopathic arthritis (JIA) are still limited though. The aim of the study was to browse the available data on microRNAs which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 96 publications
0
4
0
1
Order By: Relevance
“…In particular, we focused on the clinical characteristics of JIA patients (subtypes, disease activity, and therapies), the type of biological samples used in the different studies, and the biological characteristics of the miRNAs analyzed (free or EV-derived). The comparison between data obtained in JIA vs. adult arthritides, as well as miRNA role in JIA pathogenesis, which have been previously reviewed by others [19,112], was not further addressed here. Finally, we summarized data in the literature highlighting the relevance of miRNAs as therapeutic biomarkers in patients affected by chronic inflammatory rheumatic conditions other than JIA to emphasize the need for future research in JIA aimed at assessing miRNA potential value as predictors of responses to therapies for clinical applications in this disease.…”
Section: Mirnas In Jia: General Considerationsmentioning
confidence: 99%
“…In particular, we focused on the clinical characteristics of JIA patients (subtypes, disease activity, and therapies), the type of biological samples used in the different studies, and the biological characteristics of the miRNAs analyzed (free or EV-derived). The comparison between data obtained in JIA vs. adult arthritides, as well as miRNA role in JIA pathogenesis, which have been previously reviewed by others [19,112], was not further addressed here. Finally, we summarized data in the literature highlighting the relevance of miRNAs as therapeutic biomarkers in patients affected by chronic inflammatory rheumatic conditions other than JIA to emphasize the need for future research in JIA aimed at assessing miRNA potential value as predictors of responses to therapies for clinical applications in this disease.…”
Section: Mirnas In Jia: General Considerationsmentioning
confidence: 99%
“…Certain de ces miARN jouent un rôle important dans la régulation immunitaire (maturation et différenciation des lymphocytes T, des monocytes, polarisation des macrophage et des lymphocytes T en lymphocytes Th17, etc. ), renforçant l'hypothèse de leur implication dans cette maladie inflammatoire [27,29]. Cependant, la plupart de ces études n'ont portées que sur un nombre restreint de miARN.…”
Section: Les Micro-arn Et L'ajiunclassified
“…However, juvenile idiopathic arthritis will also occur in a high proportion, which is very detrimental to the growth of children [ 82 ]. The study has shown that miR-23b helps in the diagnosis and monitoring of RA [ 83 ]. miR-23b is negatively related to inflammation in RA [ 47 ].…”
Section: The Role Of Mir-23b In Autoimmune Diseasementioning
confidence: 99%